POTENSI ESTROGENIK EKSTRAK DAUN MAJA (AEGLE MARMELOS) TERHADAP BERAT DAN SIKLUS OVARIUM TIKUS PUTIH(RATTUS NORVEGICUS) - Rahmawati, Ima; Virda Yuniarti, Enny (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Ovary is one of reproductive organ which can be used as the indicator of mechanism of anti-fertility substance whose activities can be shown in the inhibition of ovulation and steroidogenesis. Bael leaves contains a lot of fitosterole (β-sitosterole and Stigmatosterole) of which one of its functions are hormonal contraceptive by inhibiting ovulation process.This research applied “post test only control group design plan” using random sampling. The giving of bael leaves extract to female white Rat was divided into 4 groups with the distribution: K1 as control group, K2 with a dose of 0.5 gr/kg of body weight, K3 with a dose of 1 gr/kg of body weight, and K4 with a dose of 1.5 gr/kg of body weight with a treatment of 12 days. The result of the treatment was average of lowest ovary weight at K3 and K4 were 0.04 gram, while the lowest value of the amount of cycle ovary was at K3 was 1.66. Anova onewayshowedp < 0.05, that it could be concluded that therewassignificant difference. The result of LSD test regarding ovary weight and amount of corpus luteumwerethat there was significantly difference between K1 and K3. the results showed that the bael leaf extract could be lower ovarian weight and cycle the number of rat.Keywords: bael leaves extract, ovary weight, ovary cycle